The Golden Wave : Culture and Politics after Sri Lanka's Tsunami Disaster - Gamburd, Michele Ruth, 1965- (Book collections on Project MUSE., 2014)
"In December 2004 the Indian Ocean tsunami devastated coastal regions of Sri Lanka. Six months later, Michele Ruth Gamburd returned to the village where she had been conducting research for many years and began collecting residents' stories of the disaster and its aftermath: the chaos and loss of the flood itself; the sense of community and leveling of social distinctions as people worked together to recover and regroup; and the local and national politics of foreign aid as the country began to rebuild. In The Golden Wave, Gamburd describes how the catastrophe changed social identities, economic dynamics, and political structures."--Publisher's website